Analisys Bibliometric of Science Local Wisdom with Vosviewer Application during 40 years - Dimas Fahmi Rizaldi; Muhammad Habibbulloh; Imam Sya'roni (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2025)
Objective: This study aims to analyze the development and trends in research publications related to science in the context of local wisdom, also known as science local wisdom. Local wisdom can be understood as human efforts to act and behave toward certain phenomena, objects, or events based on cognitive and cultural frameworks. Unconsciously, many forms of local wisdom inherently contain scientific elements. The objective of this research is to map and examine the academic discourse surrounding this topic through a bibliometric lens using Scopus-indexed publications. Method: The study employed a bibliometric analysis approach to explore the evolution of scientific research concerning local wisdom. This method quantitatively analyzes published literature—including journal articles, books, and other forms of written communication—based on their social, intellectual, and conceptual structures. Data were retrieved from the Scopus database and analyzed using bibliometric software tools to visualize patterns of publication, identify keyword trends, track prolific authors, and examine research collaborations. Results: The results indicate that the topic of science local wisdom is still emerging and has been receiving growing scholarly attention in recent years. The distribution of keywords and publication trends indicates that the integration of local wisdom into science education, particularly in physics learning, is becoming a growing area of research interest. However, the number of publications remains relatively low, suggesting a significant opportunity for future exploration. Novelty: This study highlights the novelty of connecting scientific literacy and education with local cultural knowledge systems. By providing a comprehensive bibliometric overview, the study not only identifies current research gaps but also emphasizes the potential of local wisdom as a culturally responsive approach to science learning, particularly within physics education. This integrated perspective offers a fresh direction for interdisciplinary educational research.